Gambaran Karakteristik Penyakit Demografi Diabetesmelitus pada Pasien di Rumah Sakit Santa Elisabeth Medan Tahun 2024 - Ayu Devitasari Simanjuntak; Indra Hizkia P; Magda Siringo-ringo; Amando Sinaga (NAJ Nursing Applied Journal, 2024)
Diabetes Mellitus is a serious disease that lasts a long time and causes disturbances in the body's metabolism, characterized by high blood sugar levels that exceed normal limits. The general aim of this research is to determine the characteristics of diabetes mellitus patients. This type of research uses total sampling, with a total of 121 respondents. The results of the research show that the characteristics of the Diabetes Mellitus patient age group are 19-39 young adults 4 respondents (3.3%), 40-59 adults 48 (39.7%), <60 elderly 69 respondents (57%). Characteristics based on gender are 75 respondents (62.0%) female, 46 respondents (38%) male. Categories based on occupation were housewives with 43 respondents (35.5%), entrepreneurs 30 respondents (24.8%), retired 20 respondents (16.5%), private sector 14 people (11.6%), farmers 8 people (6.6%), civil servants 5 people (4.1%), k. pln 1 person (8%). Characteristics based on high school education 72 respondents (59.9%), S1 37 respondents (30.6%), SMP 8 respondents (6.6%), DIII 4 people (3.3%). Based on education, namely Protestant 77 respondents (63.6%), Catholic 28 respondents (23.1%), Muslim 13 respondents (10.7%), Buddhist 3 respondents (2.5%). Based on education, Batak Toba 60 respondents (49.6%), B. Karo 36 respondents, B. Mandailing 5 respondents (5.4%), B. Simalungun 4 respondents (3.3%) Chinese 5 respondents (4.1%) , India 1 respondent (1%), Java 6 respondents (5.0%) Nias, 4 respondents (3.3%). It is hoped that it can increase knowledge and motivation about the importance of the role of nurses in managing diabetes mellitus both from the aspect of understanding the concept of self-care behavior and quality of life in diabetes mellitus sufferers.